Dialoguing for Peaceful Coexistence Among Migrants and Host Communities in Artisanal And Small-Scale Mining in Ghana (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This study examined the structures and strategies for managing and resolving conflicts that promote peaceful coexistence among migrants and host communities in Ghana's artisanal and small-scale mining sector.Design/Methodology/Approach: The study uses primary and secondary sources of data, relying on extensive document analysis, semi-structured interviews, and focus group discussions. Three communities in the Birim North District, Akoase, Noyem, and Nyafoman, were selected for this study. The snowball sampling technique was employed to select eighty young miners, comprising 50 migrants and 30 from each host community. The data were transcribed, coded, and sorted into themes using computer-based software (NVivo) to aid the overall data analysis.Research Implication: The study was limited by its inability to constitute a representative sample through random sampling procedures, which greatly affected the generalisability of the findings.Findings: The results revealed that conflicts and tensions have not led to the disintegration of relationships and communities despite their frequency. The formation of mining committees, recognition of the reciprocal benefits of collaboration, and belief in the abilities and influence of the supernatural that bestow are a few of the structures and methods for resolving disputes that promote peace.Practical Implication: The practical implications centre on the appropriateness of including migrants on mining committees as liaisons between migrants and communities. This tends to promote inclusivity, agency, and involvement in decision-making.Social Implication: The influx of migrants to gold-rich communities is often accompanied by conflicts, frequently initiated by indigenes who perceive that migrants are being granted the same rights to their lands. Despite its prevalence, this does not lead to the disintegration of relations or the communities involved. This is because the actors institute measures to resolve conflicts promptly.Originality/Value: The uniqueness of this paper aligns with the ongoing debate about the illegal mining menace in Ghana, which has led to the destruction of major water bodies and ecosystems.
Keywords: Artisanal. conflict. migrants. mining. resolution